The Effect of Implementation Socio-Scientific Issue Approach in the Context of Controversial Environmental Issues on Students' HOTS (Higher Order Thinking Skills) - Army Auliah; Jasri Djangi; Dewiyanti Fadly (Postgraduate, University of Mataram, 2024)
This research aims to see the influence of the SSI approach in the context of controversial environmental issues on chemistry students' HOTS abilities. The research method used was quasi-experimental with a post-test-only control group design. The research subjects were 26 students in class A of the chemistry education study program as the control class and 21 students in the ICP class of the chemistry education study program as the experimental class. The instruments used are observation sheets and test questions that measure students' HOTS abilities. The results of this study show that the average post-test score of the experimental class using the SSI approach was 80.15, while the average score of the control class was 60.5. The t-test shows that this difference is statistically significant with a p-value of 1.122 x 10-5, well below the 0.05 significance level. Because the p-value obtained is much smaller than 0.05, we can reject the null hypothesis (H0), which states that there is no significant difference between the two groups. These results indicate that the SSI approach in the context of controversial environmental issues has a positive influence on chemistry students' HOTS abilities in electrochemical concepts.